1728 Mass. Acts 516 - (:unkn) unknown (My University, 1728)
An Act for Repealing an Act Entitled, "An Act For The Punishing And Preventing Of Dueling," and for Making Other Provisions Instead Thereof, ch. 5: That whoever from and after the publication of this Act shall be so hardy and wicked as to fight a duel, or for private malice, displeasure, fury or revenge, voluntarily engage in a rencounter, with rapier or small-sword, backsword, pistol or any other dangerous weapon, to the hazard of life, mayhem, or wounding of the parties, or the affray of his Majesty's good subjects, although death doth not thereby ensue; or shall by word, message, or any other way, challenge another to fight a duel, or shall accept a challenge, although no duel be fought, or shall any ways abet, prompt, encourage or seduce any person to fight a duel, or to challenge another to fight
Keywords: DUELING